Feigned ambition. Analysing the emergence, evolution and performance of the ACP Group of States. Issue 4 (3rd July 2016) - Keijzer, Niels
Abstract: In 1975 the Africa, the Caribbean and Pacific (ACP) Group of States was created after the then 46 states concluded a cooperation partnership with the European Economic Community. This article draws on the literature on international organisation (IO) independence and performance to analyse the ACP Group's evolution and functioning over time. Its findings show that whereas the ACP Group has generally failed to deliver on its supra-national objectives, its members have used Group membership as a means to accessing European Union benefits. This confirms recent research that dependent and non-performing IOs may serve important funding and patronage purposes to their members.